(3GdCSaGQ Yf fJGFL GdCSaGQs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdGSaGQ KdGKI dG QGHY dgG CKHJgG GdMb YR hLd hgj SaQ ef YfOg hSaQ Edjg hSaQ ajg s
(3BNQgG (B:s
(3hjYWi GdMLI hGdbhI hGdXghQ Ydi NUeGFg hGddg jbhd GdMb hgh jgOi GdSHjd gPG BNQ GdGSaGQ hGdMeO ddg Mb MeOg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(713(2)) s
Keywords: (3GdLZQGajG h GdHdOGfs